Autonomic control of blood circulation in patients undergoing elective carotid endarterectomy - Vykoupil, Karel; Galuszka, Jan; Drac, Petr; Taborsky, Milos (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
BACKGROUND: Internal carotid artery stenosis (ICAS) is associated with significantly higher risk of stroke. Autonomic function can be impaired in the presence of atheroma in the carotid sinus region. Two parameters of autonomic nervous system (ANS) function e.g. heart rate variability (HRV) and baroreflex sensitivity (BRS) are respected predictors of cardiovascular prognosis. We assessed the effect of elective unilateral carotid endarterectomy (CEA) on cardiovascular autonomic functions as a major prognostic factor for cardiovascular health. METHODS: Nineteen patients indicated for CEA underwent formal autonomic assessment in the laboratory. Hemodynamic profiles, HRV and BRS were evaluated with the dedicated high-tech device Task Force Monitor before surgery (day-1) and postoperatively (day 3±1). Data were obtained during 5 min orthostatic challenge and subsequent 5 min in a supine position. RESULTS: There were no significant early postoperative changes in evaluated parameters after CEA. There was a mild decrease of blood pressure and therefore only a slight increase in BRS. It was also possible to observe a rise in the value of total power and high frequency power. CONCLUSION: In the early postoperative period, healing processes are occurring and the sympatho-vagal interaction is probably still unbalanced. Given the considerable clinical potential of BRS and HRV measurement, further short-term and, more importantly, long-term investigations are needed.
Keywords: baroreflex sensitivity; Humans; autonomic functions; Vagus Nerve; nervus vagus; heart rate variability; Predictive Value of Tests; Postoperative Period; Female; Aged; karotická endarterektomie; Heart Rate; výsledek terapie; sympatický nervový systém; senioři; lidé; obnova funkce; baroreflex; Baroreflex; Key words: internal carotid artery stenosis; Carotid Stenosis; ženské pohlaví; Task Force Monitor; krevní tlak; Male; srdeční frekvence; prediktivní hodnota testů; Recovery of Function; Treatment Outcome; stenóza arteria carotis; autonomní nervový systém; hemodynamika; Autonomic Nervous System; mužské pohlaví; Hemodynamics; pooperační období; Blood Pressure; Sympathetic Nervous System; Endarterectomy, Carotid